Relationship Between Verbal Abuse, Negative Attributional Style, Hopelessness and Internalizing Problems in Early Adolescence in Petaling District, Selangor - Tan, Irene Li Yin (2011)
This study examines the contribution of verbal abuse to internalizing problems among 324 early adolescent students (aged 11-13 years) in Selangor, and the mediating role negative attributional style and hopelessness play in this relationship. Students were selected using purposive sampling and data was gathered with structured questionnaire. Data was analyzed using Baron and Kenny (1986) statistical framework for assessing the mediational effects. The mediational analyses were divided into three parts in order to examine the application of extended etiological chain of hopelessness theory on these variables. In the first part, negative attributional style failed to support as a mediator between verbal abuse and hopelessness. In the second part, hopelessness was supported as a significant mediator between negative attributional style and internalizing problems. In the third part, negative attributional style was not supported as mediator between verbal abuse and internalizing problems; whereas hopelessness consistently emerged as a significant mediator in the model. Notably, the present study found that verbal abuse was directly influenced the thought of hopelessness for the onset of internalizing problems without the presence of negative attributional style. This result showed that the application of etiological chain was not supported. However, the current study made an initial step in furthering the understanding of extended etiological chain of hopelessness study regarding the development of internalizing problems. Despite the limitations, this study provides a better understanding of the influence of verbal abuse and hopelessness on internalizing problems of early adolescents in Malaysian context. The result of this study yielded the relatedness of hopelessness mind-set and resilience in the intervention of adolescents with internalizing problems. Besides, prevention work for building robust parent-child relationship must pay more attention to the appropriate communication skills between parent and child in order to effectively avoid verbal abuse.